2012
DOI: 10.1016/j.niox.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline ameliorates 2K-1C hypertension-induced vascular dysfunction in rats by attenuating oxidative stress and improving nitric oxide bioavailability

Abstract: Vascular dysfunction associated with two-kidney, one-clip (2K-1C) hypertension may result from both altered matrix metalloproteinase (MMP) activity and higher concentrations of reactive oxygen species (ROS). Doxycycline is considering the most potent MMP inhibitor of tetracyclines and attenuates 2K-1C hypertension-induced high blood pressure and chronic vascular remodeling. Doxycycline might also act as a ROS scavenger and this may contribute to the amelioration of some cardiovascular diseases associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 46 publications
3
47
1
3
Order By: Relevance
“…b , c Photomicrographs of aortas stained for collagen and elastin with Sirius red and Orceine, respectively. The techniques are described in [107] and [15]. Doxy = Doxycycline. …”
Section: Mmp-2 Induces Chronic Maladaptive Vascular Remodeling In Hypmentioning
confidence: 99%
“…b , c Photomicrographs of aortas stained for collagen and elastin with Sirius red and Orceine, respectively. The techniques are described in [107] and [15]. Doxy = Doxycycline. …”
Section: Mmp-2 Induces Chronic Maladaptive Vascular Remodeling In Hypmentioning
confidence: 99%
“…These results suggest that elevated blood pressure may be related with the "lipid peroxidation mediated" electrophysiological changes in the brain. Thus, whereas previous studies demonstrated that hypertension is associated with well known functional and structural vascular alterations that may result from the interplay of several mechanisms (21), the current study is the first to report in different hypertension models that decreased PON1 activity might be a risk factor for reduced physiological activity of the brain, in particular, in patients with chronic hypertension.…”
Section: Discussionmentioning
confidence: 53%
“…Increased ROS concentrations play an important role in the vascular dysfunction found both in clinical and experimental hypertension. High levels of superoxide react with NO in the aortic endothelium, thus reducing its bioavailability and leading to endothelial dysfunction and impaired vascular relaxation (21). The mean latencies of all VEPs components in the L-NAME group were found to be longer than those in other hypertensive groups, indicating that NO may play an important role in visual system.…”
Section: Discussionmentioning
confidence: 91%
“…Elevated reactive oxygen species-induced oxidative stress had been reported in human and different animal models of hypertension [23][24][25]. Oxidative stress causes the reduction of NO bioavailability due to removing NO by a super oxide radical and decreasing NO synthesis/release from endothelium.…”
Section: Discussionmentioning
confidence: 99%